Desjudicialização da execução fiscal e eficiência na gestão econômico-tributária: novos paradigmas para o poder judiciário - Rakauskas, Sérgio Ricardo Caires (2016)
The work presented deepens the search for better fiscal management in Brazil, especially regarding aspects of tax enforcement carried out exclusively by the judiciary. It is not today that the exclusive system of tax collection through the judiciary is questioned, that because the statistics and scientific analysis conducted by the National Council of Justice, began to highlight the alarming figures about the accumulation of tax enforcement proceedings, in particular his horrifying scale and its low degree of effectiveness. In this sense, the search for methods and ideas that can trigger an improvement in tax collection, will always be a constant by scholars in the field. The aim in this paper is an analysis of the Brazilian tax foreclosures, especially within the Union (in order to be empirical work on the case of the Union of tax enforcement already done and because the two bills studied is applied to the federal level) on three fundamental aspects for better understanding of the theme. Under the ideological aspect refers to the study of Economic Analysis of Law School (Chicago School) that aims to respond to efficientism and pragmatism proposed by the economic analysis of law can be brought into use as a method of thought to the execution of processes tax in Brazil. For it seeks to make a detailed analysis of comparative law and other sources (practices carried out in the Brazilian law and bills that promote this revitalization of the Brazilian tax enforcement) in order to find viable alternatives to changing storage paradigm tax that is now almost exclusively judicial. Under the legal aspect we check if the jurisdiction of booking is object that promotes the exclusive competence of the judiciary to carry out tax foreclosures. Be tackled in the second chapter of this work is the jurisdiction of reserves makes the procedure of tax enforcement is under the exclusive mantle of the judiciary and there is a possibility of this procedure in its entirety or at least in part, is promoted by the Executive Branch under the attribute self-execution administrative. Responding to this first premise this study aims to verify the legality and what manner consistent with the principle of reasonableness so there is the alternative charge of tax executives through the protest of outstanding debt certificates by the Treasury in extrajudicial registry offices. To verify some obstacles in this alternative form of collection, deepens the study in a case which can properly perform a management of this collection dividing those to be charged by the judiciary in a traditional way and others who should be charged for extrajudicial registry offices through the cartographic protests. Reflecting on all this context studied, tried to suggest a scope of this practical model searched for nationwide It is thus contributing to, at least, for this alternative, reduce the number of cases resulting from this particular branch of law. By last, under the procedural aspect, seeks to analyze how best to remote from judiciary. Meets this point promote an analysis of the bills that are intended to achieve the tax collection under the administrative scope, taking in large part, the tax execution procedure within the remit of the Judiciary. Given this context, are sought-ideas, methods and systems that can hold a reinvigoration of the Brazilian tax foreclosures. Among the most consistent ideas with this revitalization is the one that proposes to examine in this study, namely, the bill establishing the Tax Transaction as an alternative method of conflict resolution and better tax enforcement management and the Bill establishing the administrative implementation of the outstanding debt of the federated entities. The research method used was the hypothetical-deductive, in analyzing the legal literature.